E-Boogi Media as an Effort to Increase Knowledge of Dental Health in Junior High School Students - Putri, Chris Monica Dwi Pangesti; Erwin, Erwin (Center of Excellent (Pusat Unggulan Iptek), 2024)
Background: Knowledge about oral health is closely related to children's behavior and skills to maintain good oral health. Effective health education and promotion can contribute to positive behavior change in maintaining oral health. One of the information media that can be used to facilitate the delivery of information to readers is E-Boogi. E-Boogi (electronic dental booklet) is digital, more durable, more environmentally friendly, and more concise. Objective: To analyze the knowledge of dental health before and after counseling using E-Boogi media for seventh grade students at Junior High School. Method: This research uses a quasi experimental research design. The instrument used in data collection was a questionnaire. The sample obtained was 79 people with purposive sampling technique. Results: From the results of this study obtained knowledge of dental health before counseling using E-Boogi media which included the highest category with good criteria as many as 57 people (72.2%), sufficient criteria as many as 19 people (24.0%), and low categories with less criteria as many as 3 people (3.8%). While after counseling using E-Boogi media, the results obtained with the highest category with good criteria were 70 people (88.6%), sufficient criteria were 9 people (11.4%), and the lowest category did not exist. The average knowledge of dental health of seventh grade students at Junior High School increased from 81.51 to 91.01 with a good category. Conclusion: It can be concluded that there is an increase in dental health knowledge with counseling using E-Boogi media in Junior High School